Factors Affecting Auditor Rotation In Transportation Subsector Service Companies Listed On The Indonesia Stock Exchange - Widarti Widarti; Aries Veronica; Arin Dia Kinanti (Utan Kayu Publishing, 2025)
This study aims to analyze the effect of Public Accounting Firm (PAF) size, audit opinion, and financial distress on auditor switching in transportation service companies listed on the Indonesia Stock Exchange (IDX) for the period 2021–2024. The research method used is a quantitative approach with logistic regression analysis. The research sample consists of 27 transportation service companies selected through purposive sampling. The results show that simultaneously, PAF size, audit opinion, and financial distress significantly affect auditor switching. However, partially, these three variables do not have a significant effect on auditor switching.